Feeding and condition factor of characidiin fish in Ribeirão Grande system, Southeastern Brazil - De Souza Braga, Francisco Manoel [UNESP] (Universidade Estadual de Maringa, 2005)
Feeding, seasonal changes in visceral fat and condition factor were compared in two species of characidiin fishes, Characidium lauroi and C. alipioi from Ribeirão Grande system, southeastern Brazil. Five streams of Ribeirão Grande system were sampled (22° 47' 08 S, 45° 28' 17W). The samples were taken four times per site, from July, 2001 to April, 2002: winter (July 2001), spring (October 2001), summer (February 2002) and autumn (April 2002). Quantitative collections were made with an electro-fishing device powered by a generator with maximum capacity of 1,500 V and 8.7 A of 60 Hz alternating current. Ephemeroptera nymphs, Diptera larvae (Chironomidae, Simuliidae), Plecoptera nymphs, Trichoptera larvae (Hydroptilidae, Psychoyiidae), terrestrial insects (Coleoptera, Isoptera, Hemiptera [Heteroptera, Homoptera]), Megaloptera larvae (Corydalidae), Arachnida, Ostracoda and vegetal debris were found in both species' diets. Visceral fat declined in February, coinciding with the decline of the condition factor in both species. The increased feeding from summer to fall provides fat accumulation. During subsequent seasons, fish may utilize visceral fat reserves for maintenance and reproduction.
Keywords: Characidium alipioi; Characidium lauroi; Condition factor; Feeding; Ribeirão grande system; Stream ecology; body fat distribution; Brazil; ecology; feeding behavior; fish; herbivory; nonhuman; quantitative analysis; reproduction; river ecosystem; seasonal variation; species differentiation; stream (river); water sampling; Arachnida; Characidium; Chironomidae; Coleoptera; Corydalidae; Diptera; Ephemeroptera; Hemiptera; Heteroptera; Hexapoda; Hydroptilidae; Isoptera; Megaloptera; Ostracoda; Pisces; Plecoptera; Simuliidae; Trichoptera